Village Tourism Empowerment Against Innovation, Economy Creative, and Social Environmental - Mochamad Heru Riza Chakim; Mulyati; Po Abas Sunarya; Vertika Agarwal; Ihsan Nuril Hikam (Pandawan, 2023)
This study explores the vital role of village tourism in fostering innovation and elevating the creative economy. Through enhancing tourist experiences and advancing local innovation, it investigates the intricate impacts of village tourism on innovation, the creative economy, and society. Utilizing a qualitative approach, 145 participants are engaged via surveys to analyze factors that influence Tourism Village: Environment (En), Economic (Ec), Socio-Culture (SC), Innovation Promotion (IP), and Tourism (Tr). Employing partial quadratic-structural equation modeling through SmartPLS, it examines how citizen engagement and tourism-induced economic gains influence psychological, social, and political empowerment, and place attachment. The findings emphasize village tourism's vast potential in driving innovation, igniting creativity, and contributing significantly to economic and social growth. Nonetheless, its sustainability relies on harmonizing social, economic, and environmental aspects. The study underscores the urgency of sustainable management for lasting benefits for locals and visitors alike. Synthesizing impacts, contributions, challenges, solutions, novel insights, and revelations, this research highlights village tourism's transformative power in propelling innovation-focused advancement in the creative economy, highlighting the necessity of responsible management approaches.